Hydroxyurea (hydroxycarbamide) genotoxicity in pediatric patients with sickle cell disease. Issue 7 (7th March 2018) - Rodriguez, Anar; Duez, Pierre; Dedeken, Laurence; Cotton, Frédéric; Ferster, Alina
Abstract: Background: Hydroxyurea (HU) reduces the severity of sickle cell disease (SCD) in children; nevertheless, its long‐term safety is an important concern. This paper evaluates HU genotoxicity at dose ≤ 30 mg/kg/day after over 2 years of treatment. Procedure: The study included 76 children: 32 SCD patients treated with HU, 27 SCD patients not treated with HU, and 17 unaffected children. HU patients were classified as good or poor responders according to their clinical response. Comet assay allows the comparison of DNA damage between both groups of patients and unaffected children. Maximal concentration (Cmax ) of HU in plasma was determined after drug administration. Results: Mean values of DNA in the comet tail were 5.13 ± 6.84 for unaffected children, 5.80 ± 7.78 for patients with SCD treated with HU, and 5.61 ± 6.91 for patients with SCD not treated with HU. Significant differences were observed between unaffected children and children with SCD. No difference was evident between comets from SCD patients treated and not treated with HU. In the case of HU, mean DNA in the comet tail was significantly lower in good responders than in poor responders: 5.54 ± 7.77 and 6.69 ± 8.43, respectively. Mean Cmax value on plasma was 39.08 ± 15.65 mg/l; N = 31. Conclusions: SCD increases, slightly but significantly, DNA damage in lymphocytes from patients with SCD. Patients with SCD treated with HU do not present more nucleoid damage than patients with SCD not treated with HU. Good responders to the HU treatment have significantly less nucleoid damage than poor responders. HU treatment at ≤30 mg/kg/day does not expose patients to a genotoxic plasma concentration.